APLIKASI MOL GAMAL PADA PERTUMBUHAN DAN PRODUKSI PADI SAWAH METODE SRI (System of Rice Intensification) - Paulus, Jeanne M.; Najoan, Jemmy; Supit, Paula C. (Universitas Sam Ratulangi, 2018)
ABSTRACT The aim of the research was to studied the application of gliricidia MOL on the growth and yield of lowland rice in the SRI method, and to get the best time of gliricidia MOL application on the growth and production of lowland rice. Field research has been conducted in Tara-Tara II Village, West Tomohon Subdistrict for five months starting from June 2017 until November 2017. Treatment in the experiment consists of one treatment factor, that was interval time of gliricidia MOL application, ie : 0, 5 , 10, 15, and 20 days. The results showed that time application of gliricidia MOL have an effect on the number of productive tillers, the number of filled grain/panicle, the number of empty grain/panicle, and the dry grain yield (GKP) / plot, but not affect the plant height. The best results were achieved in gliricia MOL application on interval time every 15 days with a values were : 28.66 productive tillers; 176.90 fillet grain/panicle; 19.80 empty grain/panicle (lowest); and 9.50 kg dry grain yield or equivalent to 7.92 ton/ha.Keywords: gliricidia MOL, production, lowland rice, System of Rice Intensification (SRI)